Hot-isostatic-pressed Cr:ZnSe ultrafast laser at 2.4 μm. (October 2022) - Wang, Yuchen; Fleming, Fiona; McCracken, Richard A.; Liebig, Carl; McDaniel, Sean; Cook, Gary; Laporta, Paolo; Kar, Ajoy K.; Galzerano, Gianluca
Highlights: Kerr-lens mode-locking of hot-isostatic-pressed Cr:ZnSe polycrystal. Four optical cycles pulse generation at 2.4 μ m. Laser comparison between untreated and HIP-treated Cr:ZnSe polycrystals. Abstract: We report on a room temperature Kerr-lens mode-locked chromium-doped zinc selenide (Cr:ZnSe) laser emitting four optical-cycles pulses in the mid-infrared spectral region in which the laser polycrystal has been treated by hot isostatic pressing (HIP). The laser emits 34 fs pulses at 2.4 μ m, with a repetition rate of 171 MHz and average output power capabilities of up to 150 mW. This is the first mode-locking investigation conducted using the HIP treated material and to our knowledge, is the shortest pulse width demonstrated, to date, from polycrystalline Cr:ZnSe. The experimental comparison with respect to an untreated polycrystal indicates that HIP treatment is advantageous for mode-locking action of this active material.